Three New Species from Gunung Kanthan, a Limestone Tower Karst in Perak, Malaysia - Pei Chih, Tan Joanne; R., Kiew; L.g., Saw; A.r., Ummul-Nazrah (Phytotaxa, 2014)
Three new species, Gymnostachyum kanthanense Kiew (Acanthaceae), Meiogyne kanthanensis Ummul-Nazrah & J.P.C. Tan (Annonaceae) and Vatica kanthanensis Saw (Dipterocarpaceae), from Gunung Kanthan, Perak, are described and illustrated. All three are Critically Endangered CR B2ab (iii, iv), D1 being known from very small, restricted populations at the type locality. Gunung Kanthan is currently being quarried for cement on a large scale, which if it continues threatened all three species with extinction.